Addressing Climate Change Requires a Multidisciplinary Approach - Hamed Kioumarsi (Journal of Biotropical Research and Nature Technology, 2025)
Climate change is a globally reached problem that crosses traditional disciplinary, spatial, and societal boundaries. Facing and adaptation to climate change effects require designing a holistic approach that integrates theoretical and methodological insights from a very wide range of disciplines. This essay articulates the reasoning and critical imperative of collaborative, multi-disciplinary involvement in climate change research and action. It identifies fields where interdisciplinary coalescence elevates the level of comprehension, drives innovative problem-solving, and achieves sustainable results. It covers topics such as Recognotion of Climate Change Complexity, Environmental Contributions, Socioeconomic and Policy Scopes, Partnership and Capacity Building, as well as Challenges and Future Directions. The argument demonstrates how holistic approaches improve the precision of our decisions and strengthens global collaborations essential to realizing world sustainability goals.